Analisis Prevalensi dan Karakter Sampah Laut Pada Lokasi Wisata Pantai di Kabupaten Majene - Noor, Rahmat Januar; Mahfud, Chairul Rusyd Mahfud; Hidayah, Nur Hidayah; Hasria, Hasria; NOOR, RAHMAT; MAHFUD, Chairul; HIDAYAH, Nur (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2025)
The presence of community activities along the coast, including tourism, can be a source of marine debris. Several coastal areas in Majene Regency have been made into tourist destinations, some of which are managed by the government while the majority are not. The research conducted aims to determine the characteristics of marine debris at beach tourism locations in Majene Regency. The research method used a quantitative approach with a field survey method to collect and observe the debris found at the observation sites, namely Barane Beach and Dato Beach, over a period of 15 days. Data analysis was carried out using descriptive statistics to determine the characteristics of marine debris based on type, size, and total mass of waste, as well as oceanographic characteristics. During the research period, a total of 837 pieces of debris were collected at Dato Beach and 2,265 pieces at the northern part of Barane Beach. The analysis results showed that the dominant type of waste at both locations was plastic, primarily beverage packaging, while the majority of the debris size was meso-debris. The total mass of marine debris at Barane Beach was 173.7 kg and 15.2 kg at Dato Beach. The types of debris were significantly different, while the size did not show a significant difference. The results highlight the importance of waste management, especially at beach tourism sites. Keywords: Beach tourism, Majene, Macro-debris, Marine debris, Plastic